2020
DOI: 10.1155/2020/8886828
|View full text |Cite
|
Sign up to set email alerts
|

Nonadherence to Antiepileptic Medications and Its Determinants among Epileptic Patients at the University of Gondar Referral Hospital, Gondar, Ethiopia, 2019: An Institutional-Based Cross-Sectional Study

Abstract: Introduction. Nonadherence to antiepileptic medication is the extent of a patient’s passive failure to follow the prescribed therapeutic regimen. The prevalence and impact of nonadherence to antiepileptic medication are high globally. The main purpose of this study was to assess nonadherence to antiepileptic medications and its associated factors among epileptic patients at the University of Gondar Referral Hospital, Gondar, Ethiopia, 2019. Methods. An institutional-based cross-sectional study was conducted am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
2
10
2
Order By: Relevance
“…The present study showed that duration of epilepsy was significantly associated with medication adherence. This finding is in agreement with results of studies from Ethiopia [ 22 ], Kenya [ 19 ] and Jordan [ 18 ]. This could be due to provision of inadequate information about the course of the illness and its possible prognosis at key points during the course of epilepsy treatment [ 40 ], the side effects of antiepileptic drugs taken for a prolonged period of time [ 21 ], or simply adherence fatigue from several years of drug administration [ 41 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The present study showed that duration of epilepsy was significantly associated with medication adherence. This finding is in agreement with results of studies from Ethiopia [ 22 ], Kenya [ 19 ] and Jordan [ 18 ]. This could be due to provision of inadequate information about the course of the illness and its possible prognosis at key points during the course of epilepsy treatment [ 40 ], the side effects of antiepileptic drugs taken for a prolonged period of time [ 21 ], or simply adherence fatigue from several years of drug administration [ 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…Although stigma has been reported in previous studies as an important factor associated with treatment non adherence [ 20 , 22 ], this study has not demonstrated the association. Moreover, our study did not show an association between adherence and the presence of comorbidity in contrast to earlier findings [ 10 , 21 23 ].…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Our study agreed with other studies 33,40 who found that partial epilepsy (52%) and generalized (48%). But other study showed that 79.2% were of generalized epilepsy and 20.8% of focal epilepsy, 45 other showed that 23.1% were of generalized epilepsy and 67.5% of focal epilepsy 9.3% with uncertain epilepsy. 31 Concerning the number of medications received, our patients received AED as monotherapy (60.4% & 48.7%) more than polypharmacy (39.6% & 51.3%) among Egyptian and Saudi patients respectively.…”
Section: Discussionmentioning
confidence: 88%
“…42,43 Employers or students were less likely to adhere to their treatment regimen compared to those who were unemployed, 43 and this may be justified by working or academic schedules that prevent patients from following their prescribed regimen, or may be due to the side effects, especially drowsiness that affect job or academic performance. 44 Studies carried out in Ethiopia found that divorced and widowed patients were significantly poor adherent when compared with single patients in their marital status, 11,45 which might be due to no support from their partners in adhering to the prescribed medication(s) and instructions given by health care professionals. 11 Regarding types of epilepsy, 54.8% & 39.2% of patients with focal epilepsy versus 29.5% & 49 with generalized epilepsy among Saudis and Egyptians respectively.…”
Section: Discussionmentioning
confidence: 99%